Energy and environmental assessment of plastic granule production from recycled greenhouse covering films in a circular economy perspective. (15th January 2020) - Cascone, Stefano; Ingrao, Carlo; Valenti, Francesca; Porto, Simona M.C.
Abstract: Plastic films can be considered as a high-value auxiliary material in agriculture with multiple important uses to fulfil, including covering films in greenhouse cultivation system. Such an application enables several benefits and, therefore, it is going through an important upsurge, especially in regions where protected crop cultivation is highly widespread. However, the increased demand for these covering films arouses concerns for their post-use treatment with regard to both the consumption of Non-Renewable Primary Energy (NRPE) resources and the emission of Greenhouse Gases (GHGs). Therefore, environmental analysis is needed to find and follow cleaner paths for the management and treatment of this kind of Agricultural Plastic Waste (APW), especially in the light of the gap currently existing in the specialised literature. In this context, this paper reports upon findings from a combined Life Cycle Assessment (LCA) of single environmental issues (i.e., energy and water consumption, and GHG emissions) applied to a Sicilian firm, representative of APW collection and recycling to obtain Low-Density Polyethylene (LDPE) granules. The results showed that electricity consumption for the whole recycling process is the most NRPE resource demanding and the most GHG emitting input item. Moreover, the washing phase of disused covering films is the highest water demanding within the recycling process. Potential improvements could be achieved by shifting from fossil energy source to renewable one. The installation of a wind power plant would lead to around 56% and 85% reduction in NRPE resource exploitation and GHG emission, respectively. Finally, despite the huge consumption of water and NRPE resources and the resulting GHG emissions, the production of recycled-LDPE granules is far more sustainable than the virgin counterpart. Graphical abstract: Image 1 Highlights: Single-issue LCA was applied to recycled greenhouse covering films. The functional unit was chosen to be 1 ton of produced LDPE-granules. Primary and secondary data were inventoried. Environmental criticalities were highlighted. Improvement potentials were identified through sensitivity analyses.